Composite nonwoven materials structure, properties and applications - Das, Dipayan; Pourdeyhimi, Behnam (Woodhead publishing in textiles, 2014)
Composite nonwoven materials are versatile materials with a variety of applications, including hygiene, medicine and filtration. This important book provides a technical resource for professionals and academics in the field. It explores these materials in terms of fiber types used, manufacturing processes, structure, and physical properties